Multifunctional Roles of Green Innovation Approaches and Industry 5.0 Concert Management for Sustainable Growth in the Automotive Sectors - Muhammad Atif; Atta Ullah; Muhammad Zeeshan; Waheed Ullah Shah (Indus Journal of Social Sciences, 2025)
This study examines the automotive industry’s focus on green innovation to achieve sustainable development. The survey had 200 participants from organizations of all sizes, including small, medium, and large. It revealed a significant positive correlation (r = 0.92, p < 0.001) between green innovation practices and pressure from consumers, authorities, competitors, and previous units. In addition, a positive correlation was seen between green innovation methods and both innovation orientation (r = 0.91, p < 0.01) and performance management (r = 0.91, p < 0.01). The mediation investigation provided data that supported hypotheses H1, H4, H5 and H8. Industry 5.0 significantly affects the relationship between green innovation methods and environmental performance, with an indirect effect of β = 0.85, p < 0.001. Principal component analysis (PCA) showed innovation orientation and environmental regulation as important factors that explained 72.1% of the variation in green innovation practices. The results suggest that the adoption of Industry 5.0 and green innovation techniques can significantly influence employee behavior and environmental performance. Management organizations and industry leaders can use these results to implement sustainable practices.